Pre and post control of weedy rice and selected rice weeds with premix of imazapic and imazapyr at different ratios - Dilipkumar Masilamany,; Erwan Shah Shari,; Ng, Lee Chuen; Chuah, Tse Seng; Bhagirath Singh Chauhan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Field experiments were conducted in the rice fields of the Malaysian Agricultural Research and Development Institute in 2018 and 2019, to determine the efficacy of two commercial premix herbicides consisting of imazapic and imazapyr at 70:30 (formulation 1) and 30:70 (formulation 2) applied singly or in sequence for control of weedy rice and other rice weeds. Formulation 1 was applied as PRE at the 0 to 1-leaf stage of weedy rice while formulation 2 was applied as POST at the 3 to 4-leaf stage of weedy rice. Formulation 1 applied PRE at 150 g ai ha-1 with or without sequential application of formulation 2 applied POST at 75 or 150 g ai ha-1 provided complete inhibition of weedy rice. The same rate of formulation 1 applied PRE highly reduced weed density and dry weight of Monochoria vaginalis (99%) and Fimbristylis quinquangularis (93%) as compared to weedy check plots. Formulation 2 applied POST at 150 g ai ha-1 providing lower weed density and dry weight reduction of weedy rice (59 to 65%), M. vaginalis (80 to 81%), and F. quinquangularis (56 to 64%) as compared to those observed in formulation 1 applied PRE at 150 g ai ha-1. These results suggest that although formulations 1 and 2 share the same active ingredients, excellent control of weedy rice and rice weeds could only be achieved with PRE application of formulation 1 at 150 g ai ha-1.